The interweaving roles of mineral and microbiome in shaping the antibacterial activity of archaeological medicinal clays. (5th October 2020) - Christidis, G.E.; Knapp, C.W.; Venieri, D.; Gounaki, I.; Elgy, C.; Valsami-Jones, E.; Photos-Jones, E.
Abstract: Ethnopharmacological relevance: Medicinal Earths (MEs), natural aluminosilicate-based substances (largely kaolinite and montmorillonite), have been part of the European pharmacopoeia for well over two millennia; they were used generically as antidotes to 'poison'. Aim of the study: To test the antibacterial activity of three Lemnian and three Silesian Earths, medicinal earths in the collection of the Pharmacy Museum of the University of Basel, dating to 16th-18th century and following the methodology outlined in the graphical abstract. To compare them with natural clays of the same composition (reference clays) and synthetic clays (natural clays spiked with elements such as B, Al, Ti and Fe); to assess the parameters which drive antibacterial activity, when present, in each group of samples. Materials and methods: a total of 31 samples are investigated chemically (ICP-MS), mineralogically (both bulk (XRD) and at the nano-sized level (TEM-EDAX)); their organic load (bacterial and fungal) is DNA-sequenced; their bioactivity (MIC60 ) is tested against Gram-positive, S. aureus and Gram-negative, P. aeruginosa . Results: Reference smectites and kaolinites show no antibacterial activity against the above pathogens. However, the same clays when spiked with B or Al (but not with Ti or Fe) do show antibacterial activity. Of the six MEs, only two are antibacterial against both pathogens. Following DNA sequencing of the bioactive MEs, we show the presence within of a fungal component, Talaromyces sp, a fungus of the family of Trichocomaceae (order Eurotiales), historically associated with Penicillium . Talaromyces is a known producer of the exometabolite bioxanthracene B, and in an earlier publication we have already identified a closely related member of the bioxanthracene group, in association with one of the LE samples examined here. By linking fungus to its exometabolite we suggest that this fungal load may be the key parameter driving antibacterial activity of the MEs. Conclusions: Antibacterial activity in kaolinite and smectite clays can arise either from spiking natural clays with elements like B and Al, or from an organic (fungal) load found only within some archaeological earths. It cannot be assumed, a priori, that this organic load was acquired randomly and as a result of long-term storage in museum collections. This is because, at least in the case of medicinal Lemnian Earth, there is historical evidence to suggest that the addition of a fungal component may have been deliberate. Graphical abstract: Image 1